AT-TAHLIIL AL-MUQARIN LI AN-NAZARIYYAT AL-KALASIKIYYAH WA AL-MUASIRAH FI AL-AKHLAQ AL-IQTISADIYYAH AL-ISLAMIYYAH:: TATAWWUR MIN AL-USUS AL-MANARIYYA ILA AL-TATBIQAT AL-HADITHAH - Auliya Ghazna Nizami; Abdul Mustaqim; Moh. Mufid (Institut Agama Islam Negeri Bone, 2026)
This study provides a comprehensive comparative analysis of classical and contemporary theories in Islamic economic ethics, examining the evolution from foundational principles established by early Muslim scholars to modern applications in the global economy. Through a systematic literature review of 47 scholarly works published between 2015-2025, this research identifies key distinctions in methodological approaches, practical applications, and theoretical frameworks between classical and contemporary Islamic economic thought. Classical theories, primarily developed by scholars such as Abu Yusuf, Al-Ghazali, and Ibn Khaldun, emphasized normative foundations rooted in Quranic injunctions and prophetic traditions, focusing on local community welfare and direct moral governance. Contemporary theories, advanced by scholars like M. Umer Chapra, Monzer Kahf, and Syed Nawab Haider Naqvi, integrate traditional Islamic principles with modern economic challenges, emphasizing institutional frameworks, global applicability, and empirical methodologies. The findings reveal significant complementarity between both approaches, with classical theories providing immutable ethical foundations while contemporary theories offer adaptive mechanisms for complex modern economies. The study concludes that successful implementation of Islamic economic ethics requires synthesis of classical normative principles with contemporary institutional innovations, particularly through maqashid al-shariah frameworks that bridge traditional wisdom with modern economic realities.